2019
DOI: 10.3390/medicina55050145
|View full text |Cite
|
Sign up to set email alerts
|

Specific Urinary Metabolites in Malignant Melanoma

Abstract: Background and objectives: Melanin, which has a confirmed role in melanoma cell behaviour, is formed in the process of melanogenesis and is synthesized from tryptophan, L-tyrosine and their metabolites. All these metabolites are easily detectable by chromatography in urine. Materials and Methods: Urine samples of 133 individuals (82 malignant melanoma patients and 51 healthy controls) were analysed by reversed-phase high-performance liquid chromatography (RP-HPLC). The diagnosis of malignant melanoma was confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Valko-Rokytovská et al suggested that the following urinary metabolites can significantly contribute to the detection of melanoma: DHICA, vanilmandelic acid, homovanilic acid, tryptophan, 5-hydroxyindole-3-acetic acid and indoxyl sulphate [73]. However, the indole derivatives 6H5MI2C and 5H6MI2C are considered to be less effective than 5SCD because they are very unstable, and the analytical method needed to detect them is complicated.…”
Section: Melanin Intermediate Metabolites In Melanoma Patientsmentioning
confidence: 99%
“…Valko-Rokytovská et al suggested that the following urinary metabolites can significantly contribute to the detection of melanoma: DHICA, vanilmandelic acid, homovanilic acid, tryptophan, 5-hydroxyindole-3-acetic acid and indoxyl sulphate [73]. However, the indole derivatives 6H5MI2C and 5H6MI2C are considered to be less effective than 5SCD because they are very unstable, and the analytical method needed to detect them is complicated.…”
Section: Melanin Intermediate Metabolites In Melanoma Patientsmentioning
confidence: 99%
“…[ 29 ], but also small molecules that are precursors of eumelanin and pheomelanin, such as 5-S cysteinyldopa, 6-hydroxy-5-methoxyindole-2-carboxylic acid, 5,6-dihydroxyindole, 5,6-dihydroxyindole-2-carboxylic acid [ 30 , 31 ]. Other melanoma-related derivatives of amino acids phenylalanine and tryptophan are also described, such as vanilmandelic acid, homovanilic acid, 5-hydroxyindole-3-acetic acid and indoxyl sulfate [ 18 ]. Many of these mentioned small molecules fluoresce naturally and are also present in urine.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that, in addition to tyrosine, tryptophan and some of its metabolites are also involved in melanin biosynthesis [ 16 , 17 , 18 ]. Serotonin and its metabolite 5-hydroxyindole-3-acetic acid (5-HIAA) occurring in urine act as specific tumor markers, and increased production of 5-HIAA have been documented in human epidermal keratinocytes and melanoma cells [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indole derivatives and glycated tryptophan in rat plasma, mouse plasma, and brain were analyzed with fluorescence detection [40,41], and those in livestock urine and plasma were analyzed with LC-MS to monitor their health [42][43][44]. Valko-Rokytovska et al quantified melanin-related carboxylic compounds in human urine by HPLC-UV for the diagnosis of melanoma cancer, and found that homovanilic acid and tryptophan levels increased in the initial clinical stage of the disease [45]. Catechol-bearing carboxylic acids were separated by ion exchange chromatography, followed by derivatization with ethylenediamine and fluorescence detection [46].…”
Section: Amino Acid Metabolitesmentioning
confidence: 99%